Controlling working crowds: The impact of digitalization on worker autonomy and monitoring across hierarchical levels - Gerten, Elisa; , Michael Beckmann; Bellmann, Lutz (2018)
"The digitalization of workplace organization encourages firms to implement modern technological tools into the daily working life of employees. Innovative information and communication technologies, for instance, enable a cheaper access to work relative knowledge and a faster communication among employees. Using these ICT for professional activities promises higher performance levels. In addition, work organizations become more and more fl exible as the use of ICT decreases the neeto define total working hours (work-life blending), work places (home office) and task execution. However, digital ICT and its possible application to collect data, to record working time or to track real-time locations - to name only a few examples - foster the attractiveness of employee monitoring. This means that, on the one hand, new work arrangements due to the use of digital ICT may increase an employee's autonomy, but, on the other hand, monitoring activities might increase as well. The objective of this paper is to highlight the impact of using digital ICT devices on workplace organization. More precisely, we explore whether using digital ICT leads to more monitoring or autonomy, or to an increase in both management practices across hierarchical levels. Prior studies call attention to a forthcoming decentralization of work structures, but neglect to analyze work practices that lead to a more centralized workplace organization. However, with an increase in today's monitoring possibilities, it is important to juxtapose decentralization and centralization measures such as autonomy and monitoring, to find out which policy prevails and if there are differences of the impact of using ICT on worker autonomy and monitoring across hierarchical levels. Using new linked employer-employee data from the German Linked Personnel Panel and the IAB Establishment Panel, we applied an ordinary least squares and, additionally, an instrumental variables estimation approach to account for endogeneity issues. From the OLS estimations, we conclude that using digital ICT is positively associated with monitoring activities, independent of the employee's hierarchical position